Grain Weight Response to Different Postflowering Source:Sink Ratios in Modern High‐Yielding Argentinean Wheats Differing in Spike Fruiting Efficiency. Issue 1 (1st January 2014) - González, Fernanda G.; Aldabe, María L.; Terrile, Ignacio I.; Rondanini, Deborah P.
ABSTRACT: Improving wheat ( Triticum aestivum L.) yield potential via higher grain number per unit area (GN) may reduce average grain weight and consequently the yield increment would be low. Thirty‐nine high‐yielding modern cultivars differing in spike fruiting efficiency (FE) (number of grains per gram of no‐grain spike) were grown under potential conditions during two temperature‐contrasting years to study the level of source limitation during grain filling and rank the main physiological determinants of potential grain weight (PGW) and actual grain weight. The response of grain weight to a 100% higher source ranged from 0 to 25%, depending on cultivar and year. No general relationship was observed between PGW and FE. The stabilized grain water content, which was partially correlated with the endosperm cell number per grain ( r 2 = 48%, p < 0.05), was the main variable associated to grain weight variation ( r 2 = 77%, p < 0.00001) in both temperate and warm years. Genetic improvement focused on increasing the sink strength through higher GN is still an alternative to increase yield potential in modern cultivars as no source limitation during grain filling was observed. The improvement of FE could be used to increase GN and yield as no general negative relationship was observed between PGW and FE.